DOCK8 controls survival of group 3 innate lymphoid cells in the gut through Cdc42 activation - Aihara, Ryosuke; Kunimura, Kazufumi; Watanabe, Mayuki; Uruno, Takehito; Yamane, Nana; Sakurai, Tetsuya; Sakata, Daiji; Nishimura, Fusanori; Fukui, Yoshinori (International immunology, 2021)
DOCK8 is essential for the survival of ILC3s Abstract Innate lymphoid cells (ILCs) are a family of developmentally related leukocytes that rapidly secrete polarized sets of cytokines to combat infection and promote tissue repair at mucosal barriers. Among them, group 3 ILCs (ILC3s) play an important role in maintenance of the gut homeostasis by producing IL-22, and their development and function critically depend on the transcription factor RORγt. Although recent evidence indicates that RORγt+ ILC3s are reduced in the gut in the absence of the Cdc42 activator DOCK8 (dedicator of cytokinesis 8), the underlying mechanism remains unclear. We found that genetic deletion of Dock8 in RORγt+-lineage cells markedly reduced ILC3s in the lamina propria of the small intestine. By analyzing BrdU incorporation, it was revealed that DOCK8 deficiency did not affect the cell proliferation. Furthermore, when lineage marker-negative (Lin–) α4β7+ CD127+ RORγt– fetal liver cells were cultured with OP9 stromal cells in the presence of stem cell factor (SCF) and IL-7 in vitro, RORγt+ ILC3s normally developed irrespective of DOCK8 expression. However, DOCK8-deficient ILC3s exhibited a severe defect in survival of ILC3s under the condition with or without IL-7. Similar defects were observed when we analyzed Dock8VAGR mice having mutations in the catalytic center of DOCK8, thereby failing to activate Cdc42. Thus, DOCK8 acts in cell-autonomous manner to control survival of ILC3s in the gut through Cdc42 activation.